The role of contract incompleteness factors in project disputes: a hybrid fuzzy multi-criteria decision approach - Gurgun, Asli Pelin; Koc, Kerim (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose Contract incompleteness with deficiency, inconsistency, defectiveness, and ambiguity in contract clauses, which can cause misunderstandings and misinterpretations, may result with disputes in projects. This study aims to investigate contract incompleteness factors with a hybrid fuzzy multi-criteria decision approach. Design/methodology/approach Contract incompleteness factors were ranked by fuzzy VIKOR (Visekriterijumska Optimizacija I Kompromisno Resenje) method, and the most significant factors were subjected to fuzzy decision-making trial and evaluation laboratory (DEMATEL) to examine their causal relationships. The study is not limited to ranking the identified factors solely, since their cause-effect interactions are also essential for proper risk management in construction projects. Findings Hybrid use of multi-criteria analysis reveals that ambiguity in enforceability including excessive demands and significant amendments in the scope of works are the top two causal contract incompleteness factors, while lack of implementation details and focus of focal point, and insufficient supporting and technical documents are the most affected ones. Originality/value Contractual causes of disputes due to contract incompleteness factors other than requirements of the contracts have been rarely investigated in the literature. The research is one of the first studies in the literature investigating the causal relationship among factors in construction contracts, which might lead to project disputes. Findings are expected to improve contract drafting, eventually contributing to effective risk management in construction projects.
Keywords: Project dispute resolution; Contractual risks; Contract incompleteness; Multi criteria methods; Fuzzy VIKOR; Fuzzy DEMATEL; DEMATEL METHOD; CONSTRUCTION CONFLICT; RISK-ASSESSMENT; LIFE-CYCLE; IDENTIFICATION; MODEL; VIKOR; MANAGEMENT; RESOLUTION; SELECTION; Engineering; Business & Economics